The potential mechanisms of cardiovascular calcification in patients with chronic kidney disease - Susla, O.; Bushtynska, O.; Yakubyshyna, I.; Logoyda, L.; Symko, K.; Mysula, I. (Ukrainian Journal of Nephrology and Dialysis, 2022)
Based on current literature data, the important potential role of calciprotein particles, matrix vesicles, and extracellular matrix degradation in cardiovascular calcification mechanisms in chronic kidney disease (CKD) can be confirmed. The involvement of advanced glycation end products, insulin resistance, microRNAs, iron metabolism disorders, fluid overload, and hemodialysis treatment in these processes is discussed. It was concluded that the above potential mechanisms of ectopic calcification, which are being actively explored, are directly or indirectly related to endothelial damage/dysfunction and metabolic disturbances in the nitric oxide system. It was concluded that further thorough scientific investigations and close collaboration between clinical and experimental nephrologists are useful to optimize programs for the early detection of cardiovascular calcification, develop new effective therapeutic strategies, and improve the prognosis of CKD patients.